Efektivitas Pemungutan Pajak Bumi Dan Bangunan Perkotaan Dan Perdesaan (PBB-P2) Terhadap Peningkatan PAD Kabupaten Mamuju - callo, herman; Heryati, Yati (LPPM Universitas Muhammadiyah Mamuju, 2022)
This research takes the title of Effectiveness of Urban and Rural Land and Building Tax Collection (PBB-P2) on increasing PAD in Mamuju Regency. The purpose of this research is to know the effectiveness of collecting land and building tax in urban and rural areas (PBB-P2) on increasing PAD in Mamuju Regency. The types of data used in this research are qualitative data and quantitative data. Sources of data in this study are primary data and secondary data. The method of data collection was done through interviews and documentation. In this study using quantitative descriptive analysis techniques. The results of the research obtained are that from 2015-2019 the level of effectiveness of the realized urban and rural land and building taxes is still very far from the targeted percentage, this is obtained from the results of data processing which shows that from 2015-2019 the taxes obtained are all only reach a percentage below 50%. In 2015 the effectiveness value only reached 35.15%, in 2016 the effectiveness value only reached 38.93%, in 2017 the effectiveness value only reached 44.15%, in 2018 the effectiveness value only reached 33.15% and in 2019 the effectiveness value was only reached 39.45% and this also shows that the tax levy that entered the regional revenue agency of Mamuju Regency in that period was still in the Ineffective criteria which of course was still far from the effective criteria.